Beyond reason : postcolonial theory and the social sciences - Seth, Sanjay (Oxford: Oxford University Press, 2021)
"The knowledge that for more than a century has been disseminated by universities, and mobilized by states to govern populations, first emerged in the early modern period in Europe. It subsequently became globalized through colonialism and Western global dominance; despite the historical and cultural specificity of its origins, it was claimed to have transcended these particularities such that, unlike pre-modern and non-Western knowledges, it could be assumed to be 'universal', that is, true for all times and places. Beyond Reason traverses many disciplines, including debates in science studies, social history, art and music history, political science and anthropology, to demonstrate that the presuppositions underpinning and enabling modern Western knowledge are under sustained challenge, and that defences of a singular and universal Reason are no longer persuasive. Drawing upon and deriving its critical energies principally from postcolonial theory, Beyond Reason argues that modern knowledge and the social sciences are a product of Western modernity claiming a spurious universality: and that they embody a form of reasoning, rather than Reason itself. It proceeds to focus on History and Political Science for the further elaboration of its argument. If the social sciences are not explained and validated simply by the fact that they are 'true', it becomes possible to ask what they 'do'. Beyond Reason asks what representations and relations with the past and with politics the disciplines of history and political science enable, and what possibilities they foreclose"--
Introduction -- Part I. Modern western knowledge under challenge -- Unsettling the modern knowledge settlement -- Defending reason : a postcolonial critique -- Part II. Postcolonialism and social science -- The code of history -- The anachronism of history -- International relations : amnesia and empire -- Political theory and the bourgeois public sphere -- Epilogue. Knowledge and politics.
Includes bibliographical references and index.
Keywords: Social sciences -- Philosophy; Postcolonialism -- Philosophy; Knowledge, Theory of; Reasoning